P1-S6.15 Characteristics and predictors of women seeking rescreening for stis after using the http://www.iwantthekit.org program: were they infected or uninfected?. (10th July 2011) - Gaydos, C; Hsieh, Y H; Barnes, M; Jett-Goheen, M; Quinn, N; Agreda, P; Whittle, P; Hogan, T
Abstract : Background: CDC recommends rescreening women who are infected with chlamydia (CT) and gonorrhoea (GC) in 3 months. The iwantthekit (IWTK) Internet screening program offered an opportunity to study women who seek rescreening, and determine reported infected status at the previous screening. Mailed IWTK home-collected vaginal swabs are tested for CT, GC, and trichomonas (TV) by NAATs. Methods: Characteristics (demographics, risk behaviours, use perceptions) of repeat users were determined from questionnaires. Predictors of repeat users were measured in a matched case-control study by conditional logistic regression analysis. A case (N=304) was defined as reporting having ever used IWTK before. A control was a user who reported never using the program earlier. Two controls (N=608) were systematically sampled for each case by matching date of use of IWTK of the case within 3 months. Results: From 2007 to 2010, 17% of 1747 women who used IWTK for STI testing indicated they had used IWTK previously. Of these, 45% used it >2 times. Mean age was 24.7±5.7 yr; most were African American (69%); single (87%); 57% had 2–4 sexual partners previous yr; 44% had new partners in last 3 months; 32% were currently having sex >1 person; 16% practiced anal sex in the last 3 months; 13% never used condoms; 77% had been treated for an STI; (5 HIV+). In multivariate analysis, repeat IWTK users were more likely to be ≥20 yr. (OR=2.10, 95% CI 1.30 to 3.38) and reside in Maryland (OR=2.03, 95% CI 1.31 to 3.13). They were more likely to have had a pelvic exam in past yr (OR=2.03, 95% CI 1.36 to 3.05); be treated for an STI (OR=2.32, 95% CI 1.57 to 3.44); to perceive internet screening as confidential (OR=1.98, 95% CI 1.32 to 2.97); report results from self-administrated swabs as accurate (OR=2.49, 95% CI 1.61 to 3.87); be less likely to drink alcohol before sex (OR=0.63, 95% CI 0.44 to 0.91); and to never use condoms with vaginal sex (OR=0.43, 95% CI 0.27 to 0.69). Of repeat users, 84.2% reported having a negative prior test and 48/304 (15.8%) reported last test positive; 27 had CT; 24 had TV; 3 had GC; 6 were mixed infections. At present test, 40 (13.2%) were positive: 14 had CT, 2 had GC, 28 had TV; 4 were mixed infections. Previous TV was associated with current TV positivity (p<0.05). Conclusions: IWTK attracted many previous participants who practiced high-risk sexual behaviours to use IWTK for repeat STI testing. IWTK may offer an alternate approach for rescreening previously infected women.